(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aims to explore the relationship between alcoholism among college students and their academic performance. The results suggest that being an alcoholic user can have a negative impact on academic performance, leading to lower grades, increased absences, and difficulty focusing. It is important for college students to provide resources and support for students struggling with alcohol use to improve their academic success and overall well-being. The results of the survey showed that the majority of the respondents are between the ages of 18 and 27, and 48% are male and 52% are female. The research created a guide to give them possible factors affecting being alcoholic among college student and their academic performance. Thus, the study recommends that college students focus on their studies instead of drinking alcoholic beverages. Based on our survey, we discovered that drinking alcohol makes them unwell, which has an impact on their academic performance. Students in college drink not just to relieve stress or deal with problems but also to have fun or celebrate. Our suggestions are well-accepted by many college students who want to stop consuming alcohol.